CHILDREN AT RISK: SOCIAL POLICIES AND SERVICES AND THEIR IMPACT IN ALBANIA - Kulluri, Eliona Bimbashi; Allmuça, Marsela (Ревија за социјална политика/Journal of Social Policy, 2015)
Albania society has experienced a prolonged transition which is accompanied with substantial changes that have caused effects on families and especially children’s lives. Groups of children at risk of social exclusion in Albania are: working and street children, children in conflict with law, poor children, Roma children, children who are subjected to violence and trafficking, children involved in the phenomenon of the blood feud, children with disabilities and children living in rural areas. This categories shares very difficult experiences such as living in minimal conditions, suffer lack of access to key services such as lack of health services, very low attendance and lack of access to educational institutions. These consequences associate with lack or inadequacy of appropriate service provision and lack of coordination between the responsible structures. The purpose of this study is to analyze the situation of children at risk in Albania, policies and services for this category, their impact as well. For the realization of the study are used methods of secondary data analysis combined with qualitative data provided through semi-structured interviews with key persons in different decision-making level, and focus groups with children at risk. Key findings are related with lack of policies to address the prevention, protection, assisted voluntary return, repatriation and reintegration of trafficked children; gaps in the implementation of the National Action Plan to Combat Trafficking in Children; lack of coordination between institutions and services; services and programs at central and local level for children as Children Protection Units are not spread across all the territory; there is a reduction in the number of residential and day services and increase of community once, etc. Research findings conclude with the need for improved social care legislation and creating of suitable legal acts, which emphasizes the role of stakeholders in supporting children; Foreseen policies that address the prevention, protection, assisted voluntary return, repatriation and reintegration of trafficked children; to include the elimination of child labour in general policies and national programs; creating multi-sectoral mechanisms to identify victims of trafficking, especially trafficked children, etc.